Patologija kronične vnetne črevesne bolezni - Dolenc-Stražar, Zvezdana (Medicinski razgledi, 2010)
The article shows a histopathological review of inflammatory bowel disease (IBD) and the associated neoplasia. Its etiology is stilI not well defined andit involves genetic susceptibility, abnormalities in the gut epithelium, gut bacteria, and dysregulation ofhost's immune response. Its incidence is higher in the developed world and is stil! growing. Most cases of IBD compriseulcerative colitis and Crohn's disease, and the remaining 5-15% involve indeterminate colitis. In the differential diagnosis, colitis induced by nonsteroidal antiinflammatory drugs, ischemic colitis, radiation colitis, infectious colitis, graft versus host disease, and colitis associated with diverticular disease need to be excluded. Patients with long-term disease havean increased risk of developing neoplasia and after 10 years with this disease the carcinoma risk increases by 1-2% each year.
Keywords: črevesje; diagnostika; vnetja; kronična vnetna črevesna bolezen; ulcerozni kolitis; Crohnova bolezen; karcinom; histopatologija; therapy; zdravljenje